Study of the variations in apoptotic factors in hippocampus of male rats with posttraumatic stress disorder - Behrang Alani; Nader Maghsoudi; Ali Khatibi; Mahdi Noureddini; Farzad Asefifar; Jamal Shams (Advanced Biomedical Research, 2013)
Background: Post-traumatic stress disorder (PTSD) is a stress-related psychosomatic disorder caused by occurrence of a traumatic event and the hippocampus volume of the patients with Post-traumatic stress disorder decreased. However, the mechanisms that cause such damage are not well-understood. The aim of this study is to detect the expression of apoptosis-related Bax, Bcl-2, Caspase-3 and Insulin-like growth Factor-I proteins in the hippocampus region in the Predatory stress rats. Materials and Methods: A total of 70 male wistar rats were divided into Predatory stress groups of 1d, 2d, 3d, 7d, 14d, 30d and a normal control group (N = 10). Rats were subjected to 5 min of predatory stress and then exposed to the elevated plus-maze (EPM). Serum corticosterone and Insulin-like growth factor-1 level of Hippocampus were measured by ELISA technique. The expression of Bax, Bcl-2, and Caspase-3 were detected by western blotting. Results: Rats spent significantly more time in closed arms of the elevated plus maze (EPM) than control group after exposure to stress. Serum levels of corticosterone significantly increased at 2d-3d. The expression of hippocampal IGF-1 was significantly up-regulated at 1d-2d after stress. Both Bax and the ratio of Bax/Bcl-2 significantly peaked at Predatory stress 2d-14d. Caspase3 was significantly active among 2d-30 compared to the normal control. Conclusion: The activation of caspase-3 in the stress groups indicates that apoptosis may be one of the reasons inducing hippocampus atrophy and play roles in the pathogenesis of PTSD. Increase in hippocampus levels of IGF-1 during early PTSD might be involved in the early molecular inhibitory mechanism of apoptosis in PTSD.